Exploring the Utilization of Social Media Channels for Indonesian Islamic Economic Development - Muwaffaq, Muhammad Aunul; Mahsyar, Nun Maziyyah (ITB AAS INDONESIA Surakarta, 2024)
The global expansion of Islamic economics has been steadily growing. Several causes are contributing to this phenomenon, with the use of social media being a significant driver in promoting literacy. The Islamic Economics Society Association, often known as MES, has successfully expanded its network throughout Indonesia and internationally to promote Islamic economics and finance. This study seeks to investigate the capacity of social media used by MES in disseminating Islamic financial knowledge. This study will utilize qualitative analysis using a literature-based approach. The data will be collected by conducting a thorough examination of the potential and influence that has been achieved in social media. This will be done by analyzing the qualitative analysis model developed by Miles and Huberman, specifically focusing on data reduction, display, and conclusion. The study revealed that the use of social media can augment the literacy and inclusivity of society about Islamic economic and financial knowledge, leading to a transition towards the halal lifestyle and an enhancement of the human development index.